Viruses identified in endomyocardial biopsy samples in idiopathic dilated cardiomyopathy patients in central South Africa - Hanekom, H.A.; Makotoko, E.M.; Botes, L.; Brown, S.C.; Baumeier, C.; Schultheiss, H.-P.; Smit, F.E. (SA Heart Journal, 2025)
Background: Heart failure and cardiomyopathy are problematic in South Africa. Viruses are important causes of myocarditis and cardiomyopathy. This study aimed to determine the distribution of viruses in endomyocardial heart biopsy samples in patients with dilated cardiomyopathy. Methods: Endomyocardial biopsies (EMB) were analysed using histology, immunohistochemical staining, and polymerase chain reaction. The level of fibrosis, presence and type of cellular infiltration, and the prevalence of viral genomes with their replication activity were determined. Results: Viral genomes were found in 73.7% of patients, with parvovirus B19 (B19V) present in 96.4%. No Coxsackievirus was identified, and 2 patients presented with transcriptional intermediates, which indicated active B19V viral replication. Most patients (71.4%) presented with single infections, but some (28.6%) with co-infections. Three patients presented with acute myocardial inflammation and moderate / severe increased lymphocytic infiltration. Conclusions: This study found B19V predominant and present in almost all virus-positive EMB samples. Our results support the possible virus etiological shift towards B19V. These findings underscore the need to further investigate the pathophysiological role of B19V in the development and progression of DCM.